Pembelajaran IPS Melalui E-Learning Berbasis Google Form Terhadap Hasil Belajar Siswa Kelas V SD - Anisa Fitria; Veryliana Purnamasari; Qoriati Mushafanah (STKIP Andi Matappa Pangkep, 2022)
The purpose of this study was to determine whether or not the social studies learning through e-learning based on google form on the learning outcomes of fifth graders at SDN 01 Kebondalem Pemalang. The research method used is quantitative research with research design using Pre-Experimental Design. The type of design used is a one group pretest-posttest design. The population of this research is the fifth grade students of SDN 01 Kebondalem Pemalang. Samples were taken by 36 students, with 11 male students and 25 female students using a non-probability sampling technique with saturated sampling type. Data collection techniques in this study were obtained through interviews, observations, tests and documentation. From the pretest value, it shows that the average value is 53.33 while the posttest value shows that the average value is 82.91 and based on the t-test analysis, it is obtained that tcount is 9.227 with t of 2.028. The learning outcomes of students before and after being treated are not the same. The analysis of learning mastery before being given treatment was 19%, while after being given treatment it was 83%.